The effect of cannabidiol on seizure features and quality of life in drug-resistant frontal lobe epilepsy patients: a triple-blind controlled trial - Ebadi, Seyyed Reza; Saleki, Kiarash; Adl Parvar, Tanin; Rahimi, Negin; Aghamollaii, Vajiheh; Ranji, Sara; Tafakhori, Abbas (Frontiers in Neurology, 2023)
Background Treatment-resistant epileptic seizures are associated with reduced quality of life (QoL). As polypharmacy with routine antiseizure medications has many side effects, novel add-on treatments are necessary. Recent research showed the efficacy of add-on therapy by cannabidiol (CBD) on refractory epilepsy. We attempted to extend data on the efficacy and safety profile of CBD in patients with frontal lobe treatment-resistant epilepsy. Methods A total of 27 patients were recruited into two CBD (n = 12) and placebo (n = 15) groups. The CBD group received a highly purified liposomal preparation of the drug in addition to routine antiseizure medications. The placebo group only received antiseizure medications. This experiment followed a triple-blinding protocol. Outcome measures were seizure frequency, the Chalfont seizure severity scale (CSSS), and the quality of life questionnaire score (QOLIE-31) assessed at baseline, 4 weeks, and 8 weeks. Results At 4 weeks, results indicated that a higher fraction of patients in the CBD group (66.67%) showed improvement in seizure, compared to the placebo group (20.00%). Before–after comparison revealed that CBD, unlike routine ADEs, was effective in reducing the occurrence of seizures at the study's final timepoint [mean difference 45.58, 95% CI (8.987 to 82.18), p = 0.009]. Seizure severity was not affected by study groups or time intervals (repeated-measures ANOVA p > 0.05). Post-hoc tests found that the QoLI-31 score was improved at 8 weeks compared to baseline [mean diff. −5.031, 95% CI (−9.729 to −0.3328), p = 0.032]. The difference in cases who experienced enhanced QoL was meaningful between the CBD and placebo groups at 8 weeks [RR: 2.160, 95% CI (1.148 to 4.741), p = 0.018] but not at 4 weeks (p = 0.653). A positive finding for QoL improvement was associated with a positive finding for seizure frequency reduction [r = 0.638, 95% CI (0.296 to 0.835), p = 0.001]. Interestingly, limiting the correlation analysis to cases receiving CBD indicated that QoL improvement was not linked with seizure parameters such as severity and frequency (p > 0.05). Conclusion The present study suggests the benefit of a purified and highly efficient preparation of CBD for seizure frequency reduction and improvement of QoL in refractory frontal lobe epilepsy. Further study with longer follow-ups and larger sample size is advised. Clinical trial registration https://www.irct.ir/trial/56790, identifier: IRCT20210608051515N1.